Analysis of clinical practices related to anticipatory menstrual education for adolescents - Schehr, Lindsay K. (My University, 2012)
Aims and objectives. This study aimed to describe nurse practitioners awareness of the established guidelines for menstrual anticipatory education; to investigate practitioner?s routine use of these established guidelines; and finally, to examine and describe nurse practitioners approach in educating adolescents about the signs, symptoms, and onset of menarche. Background. Menarche marks a significant milestone as the beginning of a woman?s reproductive life. The lack of comprehensive, age-appropriate information leads to misconceptions and contributes to menarche being a traumatic and uncomfortable experience. Nurse practitioners are in unique positions to provide current and accurate information related to menarche. Intentional practice guidelines are in place for clinicians surrounding anticipatory menstrual education. However, the actual awareness and utilization of clinical guidelines for anticipatory menstrual education by nurse practitioners is unknown. Design. A descriptive design was utilized to determine current awareness of established guidelines for menstrual anticipatory education and to investigate and describe routine use of these guidelines; and secondly, to examine and describe other approaches in educating adolescent girls about the signs, symptoms, and onset of menarche. The conceptual framework for this study was Peplau?s Theory of Interpersonal Relations. The nurse-patient relationship is established to meet the needs of individuals, and interactions are aimed at enhancing patient well-being. Methods: A convenience sample of 33 (n=33) advance practice nurse practitioners from a northeastern state were recruited and surveyed. A 27-item questionnaire was developed and administered using Qualtrics online survey software. The survey included 23 closed-ended questions about anticipatory menstrual education and 4 narrative questions about other educational approaches utilized. Results. The sample consisted primarily of women (n=30, 90.9%), ranging in age from 24 to 55 years and older, with the majority of participants 46 to 55 years of age (n=14, 42.4%). All participants held a professional degree in advanced practice nursing, 93.9% (n=31) held a master?s degree in nursing, with 6.1% (n=2) listing ?other.? Only 75% (n=25) of the APRNs surveyed provided anticipatory menstruation education to adolescent girls; 51.4% of APRNs that provided anticipatory menstrual education were not aware that guidelines existed. The majority of participants (n=16, 48.5%) provided anticipatory menstrual education between 11 and 13 years of age. During menstrual education, participants reported 100% parental presence; however, it was reported that the majority of parents do not solicit anticipatory menstrual education. APRNs identified types of education they provided to adolescents regarding menarche ? 100% provided information related to physical developmental changes (n= 25), 72% provided information on pain management (n= 18), and 44% provided information on feminine product choices and usage (n=11). Conclusions. Analyzing the research data revealed three significant findings: lack of knowledge related to anticipatory menstrual education, struggle to provide comprehensive menstrual education, and lack of standardized menstrual questions on physical and gynecologic examination forms. Clinical Relevance. It is crucial that APRN?s are aware and utilize the anticipatory menstrual education guidelines for adolescents. Instead of relying on school programs to provide menstrual education, APRN?s need to understand the menstrual education they can provide is not interchangeable. APRNs are essential in providing information about the physical discomfort, sanitation issues, and the emotional and social impact of menarche. There is an obvious need for young adolescents to be prepared prior to menarche, and APRNs should be an integral part of the educational process.
A Clinical Paper Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing Family Nurse Practitioner
Keywords: Adolescence; Menstruation; Teenagers - Health and hygiene; Health education (Middle School)